A first Model of Fatigue Corrosion of a Metal through Hydrogen Embrittlement. Issue 1 (25th January 2021) - Hofmann, Martin; Shi, Yuhao; Wallmersperger, Thomas
Abstract: Predicting the durability of components under mechanical loading combined with environmental conditions leading to corrosion is one of the most challenging tasks in mechanical engineering. Precise predictions are neccesary for lightweight design in transportation due to environmental protection. During corrosion often hydrogen is produced by electrochemical reactions. Hydrogen embrittlement is one of the most feared damage mechanisms for metal constructions leading to early and unexpected failure. Until now predictions are mostly done through costly experiments. In the present research, a first simple simulation model based on the fundamentals of electrochemistry and continuum damage mechanics is developed to couple the damage induced by the mechanical stress with the hydrogen embrittlement. Results of the durability are presented for the case of uniaxial cyclic loading for varying testing frequency.